Comparison of electromyogram reaction time at the onset of motion in badminton players at different competitive levels - Masu, Y.; Otsuka, A. (Journal of Human Sport & Exercise, 2022)
In this study, we evaluated the electromyogram reaction time of femoral muscles at the onset of motion in college badminton players at different competitive levels, with the aim of clarifying the characteristics of the motor reaction processing in response to stimulation. The participants were seven male players from the team that won second place in the All Japan College Badminton Championship (high-performance group) and college badminton players with no experience in participating in national championship games (low-performance group). In both the 1-direction and 2-direction tasks, the action time was shorter, and the pre-motor time of femoral muscle activity was significantly shorter in the high-performance than in the low-performance group. In both tasks, significant differences were observed in the rate of increase in absolute EMG amplitude of the swing-out and push-out legs, and the values were higher in the high-performance than in the low-performance group. Results indicate that high-performance badminton players are able to move quickly by synchronizing the motor units of the rectus femoris muscle at the onset of motion and perform actions by exerting large joint torques.